النوافذ المصرفية الإسلامية خطوة نحو الصيرفة الإسلامية دراسة حالة بنك الفلاحة والتنمية الريفية BADR الوادي - زين الدين, زغيب; عيسى, فاسي; عبد اللطيف, حمادي (جامعة الوادي - University of Eloued, 2023)
تهدف الدراسة إلى تحديد ماهية النوافذ المصرفية الإسلامية كخطوة نحو الصيرفة الإسلامية ببنك الفلاحة والتنمية الريفية ، وقد حاولنا الإجابة عليها من خلال افتراض أن النوافذ الإسلامية مدخل مهم لتحول البنوك نحو الصيرفة الإسلامية و مساهمة شباك الصيرفة الإسلامية بشكل كبير في بنك BADR-الوادي على تفعيل الصيرفة الإسلامية. وتوصلت نتائج الدراسة إلى وجود دور ومساهمة للنوافذ الإسلامية في زيادة أرباح البنوك و يعتبر مشروع النوافذ الإسلامية في بنك badr تجربة ناجحة.The study aims to determine the nature of Islamic banking windows as a step towards Islamic banking at Bank for Agriculture and Rural Development, We have tried to answer it by assuming that the Islamic windows are an important entry point for the shift of banks towards the Islamic banking system and the significant contribution of the Islamic banking window of BADR-Wadi Bank to the activation of the system Islamic banking. The results of the study concluded that there is a role and contribution of Islamic windows in increasing the profits of banks, and the Islamic windows project at Badr Bank is a quintessential successful.
Keywords: نوافذ مصرفية، صيرفة إسلامية، بنك الفلاحة والتنمية الريفية; Islamic banking, Bank for Agriculture and Rural Development